A Survey of Transport Simulation Tools - Comparing free tools for simulating autonomous vehicles in traffic and logistics networks - Hultén, Jonas. A. (My University, 2019)
With the emergence of autonomous transport vehicles it becomes desirable to simulate and evaluate their behavior before they begin operating on the open road. In this work we study three simulator platforms for traffic and logistics simulation and evaluate them over eleven criteria and three scenarios. We find that none of the simulators is strictly better than any of the others, instead excelling in handling different classes of problems, such as simulation of goods transport or fuel consumption estimation.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science